Evaluation of levels and sources of microplastics and phthalic acid esters and their relationships in the atmosphere of highly industrialized and urbanized Gebze, Turkiye - Celik-Saglam, Isil; Yurtsever, Meral; Civan, Mihriban; Yurdakul, Sema; Çetin, Banu (Elsevier, 2023)
The presence of microplastics (MPs) in the atmosphere and their relationship with other pollutants have been gaining attention due to both their ubiquity and threatening human health. As well phthalic acid esters (PAEs) regarding as plasticizers for being added in plastic materials are key role for plastic pollution. In this study, the concentrations and sources of airborne MPs together with major PAEs and their relationships were investigated for four seasons. MP particles <20 mu m, constituting the majority of the samples, were successfully revealed by NR fluorescent analysis. As a result of the mu ATR-FTIR analyzes, it was seen that besides different polymer derivatives, dye-pigment types, some minerals and compounds, and abundant semi-synthetic fibers and natural fibers were also present. MPs concentration were found in the range of 7207-21,042 MP/m(3) in summer, 7245-32,950 MP/m(3) in autumn, 4035-58,270 MP/m(3) in winter and 7275-37,094 MP/m(3) in spring. For the same period, the concentrations of PAEs ranged from 9.24 to 115.21 ng/m(3) with an average value of 38.08 +/- 7.92 ng/m(3). PMF was also applied and four factors were extracted. Factor 1, accounts 52.26 % and 23.27 % of the total PAEs and MPs variances, was attributed to PVC sources. Factor 2, explaining 64.98 % of the total MPs variance had the highest loading of MPs and moderate loadings of relatively low molecular weight of PAEs, was attributed to plastics and personal care products. Factor 3, explaining the 28.31 % of the total PAEs variance was laden with BBP, DnBP, DiBP and DEP and was attributed to various plastic input during the sampling campaign coming from the industrial activities. The last factor accounts for 11.65 % of the total PAEs variance and was dominated by DMEP and it was linked to a source of the activities performed in the laboratories of the university.
Keywords: Air pollution; Microplastics; Phthalic acid esters; Correlation; Positive matrix factorization; NR fluorescent